Residual efficacy of cypermethrin and pirimiphos-methyl against Sitotroga cerealella (Olivier) in wheat grain - Pražić Golić, Marijana; Kljajić, Petar; Andrić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Residual efficacy of EC formulations of two insecticides: cypermethrin supplemented with the synergist piperonyl butoxide, and pirimiphos-methyl, against adults of the Angoumois grain moth, Sitotroga cerealella (Olivier), was investigated in the laboratory (at 25±1°C and 55-60% r.h.) by applying water solutions of products based either on cypermethrin (1.6 mg a.i./kg of wheat grain) or pirimiphos-methyl (4 mg a.i./kg of wheat grain) to wheat grain. Insect mortality on deposits of different age: 0, 7, 14, 30, 60, 90, 120, 150 and 180 days was estimated after 2, 7 and 14 days of insect exposure to treated wheat. After 2 day exposure, cypermethrin caused mortality of up to 46% on all deposits (age 0-180 days). After 7 days of exposure, high efficacy (94-100%) was found only on deposits that were up to 90 days old, while the mortality of S. cerealella adults on all deposits following 14 days of exposure was 98-100%, and it was probably additionally enhanced by natural mortality. Pirimiphos-methyl was 98-100% effective after 2 days of exposure to deposits that were up to 30 days old, while it achieved maximum efficacy (100%) after 7 days of insect exposure to deposits aging for up to 150 days, and 94% efficacy on 180 days old deposits. After 14 days of adult exposure to all deposit ages, there were no surviving insects (efficacy 100%). The results show that pirimiphos-methyl was more effective against S. cerealella adults and had a longer residual activity than cypermethrin.
Keywords: Sitotroga cerealella; Cypermethrin; Pirimiphos-methyl; Residual efficacy; Wheat